PENGARUH LINGKUNGAN KELUARGA DAN MINAT BELAJAR TERHADAP HASIL BELAJAR EKONOMI SISWA SMAN KECAMATAN KOTO TANGAH KOTA PADANG - Rizka Atikah (Universitas Negeri Padang, 2018)
The research aims to find out the influence of family environment and learning interest on the economics learning outcome of students grade X-XI SMAN, Koto Tangah district, Padang. The type of this research is descriptive and associative. The population of this study amounted to 1.195 people and the number of the samples is 90 people. The sampling technique is done by using Cluster Sampling with multi stage cluster sampling. The technique of data collection is by questionnaire. The data analysis used is descriptive analysis. Data analysis technique used is multiple linear regression. The result showed that there was a significant positive effect between family environment and learning interest on the economics learning outcome. Based on the results of the research to improve student learning outcomes in SMAN Koto Tangah district Padang, it is advisable for parents to improve good relationships with the students, therefore, the students feel comfortable and quiet during learning. For teachers it is expected to apply learning methods that make students become active and interested. For students the way of learning for further improvement is needed in order to get better learning outcomes than ever.Keyword: family environment, learning interest, learning outcome